Biliary Dyskinesia in Children and Adolescents: A Mini Review - Simon, David A.; Friesen, Craig A.; Schurman, Jennifer V.; Colombo, Jennifer M. (Frontiers in Pediatrics, 2020)
Introduction While functional gallbladder disorder is a well-recognized and defined condition in adults, its pediatric analog, biliary dyskinesia, lacks uniformity in diagnosis. Yet, biliary dyskinesia is among the most common conditions resulting in cholecystectomy in youth and its frequency continues to rise. The primary aims of the current review were assess the efficacy of cholecystectomy in children diagnosed with biliary dyskinesia and the utility of cholescintigraphy in predicting outcomes. Results All previous studies assessing outcomes in youth with biliary dyskinesia have been retrospective and therefore of low quality. There is a lack of uniformity in patient selection. Short term follow-up reveals partial response in 63.4-100% with complete resolution in 44.2-100%. Only 4 studies have reported long-term outcomes with complete symptom resolution in 44-60.7%. The published research generally indicates that the gallbladder ejection fraction (GBEF) as determined by cholescintigraphy lacks utility in predicting cholecystectomy outcome utilizing the commonly used cut-off values. There are data suggesting that more extreme cut-off values may improve the predictive value of GBEF. Conclusion There is a lack of consensus on the symptom profile defining biliary dyskinesia in youth and current literature does not support the use of cholescintigraphy to select patients for cholecystectomy. There is a substantial portion of pediatric patients diagnosed with biliary dyskinesia who do not experience long-term benefit from cholecystectomy. Well-designed prospective studies of surgical outcomes are lacking. Increasing the uniformity in patient selection, including both symptom profiles and cholescintigraphy results, will be key in understanding the utility of cholecystectomy for this condition.